2016
DOI: 10.1002/slct.201600947
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Mechanistic and Synergistic Aspects of Novel Synthetic Short Cationic Antibacterial Peptides

Abstract: Two series of short cationic antimicrobial peptides (CAMPs) in which modification of the imidazole ring of histidine by bulkier alkyl substituents was done using regiospecific and radical‐mediated alkylation. The synthesized CAMPs were evaluated for their antibacterial efficacy using different bacterial strains. In particular, CAMP 11 i was found to be most active against L. monocytogenes and other CAMPs such as 10 e and 11 g exhibited moderate activity against S. aureus.The most active compounds were tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…It was suggested that this class of peptides act by selectively binding to negatively charged microbial membranes over the neutral mammalian membranes, and disrupt the cell membranes leading to lysis of the microbial cells. 144 Mittal et al 145 reported another class of modified histidine containing short cationic antimicrobial peptides (Figure 8). Peptides were screened against S. aureus, Listeria monocytogenes, E. coli, Vibrio cholerae and Enterococcus 165 showed the most significant activity against L. monocytogenes with IC 50 values of 9.3 μg/ml, but was inactive against all other strains.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…It was suggested that this class of peptides act by selectively binding to negatively charged microbial membranes over the neutral mammalian membranes, and disrupt the cell membranes leading to lysis of the microbial cells. 144 Mittal et al 145 reported another class of modified histidine containing short cationic antimicrobial peptides (Figure 8). Peptides were screened against S. aureus, Listeria monocytogenes, E. coli, Vibrio cholerae and Enterococcus 165 showed the most significant activity against L. monocytogenes with IC 50 values of 9.3 μg/ml, but was inactive against all other strains.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Mittal et al 145 reported another class of modified histidine containing short cationic antimicrobial peptides (Figure 8). Peptides were screened against S. aureus , Listeria monocytogenes , E. coli , Vibrio cholerae and Enterococcus faecalis .…”
Section: Importance and Applications Of Histidine And Ring‐modified H...mentioning
confidence: 99%
See 2 more Smart Citations